STRENGTH ANALYSIS OF COMPOSITE MATERIALS IN HIGH SPEED AIRCRAFT STRUCTURES - Edison Hatoguan Manurung; Pio Ranap Tua Naibaho; Fahmy Hermawan; Sarjono Puro; Yuwono Imanto (Yayasan Adra Karima Hubbi, 2025)
The aviation industry increasingly relies on composite materials to optimize performance and reduce weight in high-speed aircraft structures. These materials offer superior strength-to-weight ratios, corrosion resistance, and design flexibility. Understanding the mechanical properties of composite materials is essential for enhancing the safety and efficiency of high-speed aircraft. This research aims to analyze the strength characteristics of composite materials used in high-speed aircraft structures. The study focuses on evaluating the mechanical properties and performance under various loading conditions to determine their suitability for aviation applications. An experimental approach was employed, involving the fabrication of composite samples using different matrix and fiber combinations. Tensile, compressive, and flexural tests were conducted to assess mechanical properties. Data were collected and analyzed to evaluate the performance of each composite configuration under simulated operational conditions. The findings indicated that hybrid composite materials exhibited the highest strength and stiffness, outperforming traditional materials. The tensile strength of the best-performing composite reached up to 600 MPa, while flexural tests showed significant resistance to deformation. These results highlight the potential of advanced composites to enhance the structural integrity of high-speed aircraft. The research underscores the importance of selecting appropriate composite materials for high-speed aircraft applications.